1997
DOI: 10.2307/2953380
|View full text |Cite
|
Sign up to set email alerts
|

Urban Adolescent Females' Views on the Implant and Contraceptive Decision-Making: A Double Paradox

Abstract: Focus groups and in-depth interviews were used to explore the decline in popularity of the contraceptive implant in a clinic-based sample of 41 ethnically diverse, urban, sexually active adolescents. While these teenagers' socioeconomic status and patterns of inconsistent contraceptive use made them potentially ideal implant recipients, they were unlikely to select this method. Negative media reports about the method were less influential than social conditions such as peer perspectives and gender relations. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 19 publications
0
63
1
Order By: Relevance
“…Similar to the findings of a 1997 study of adolescents using Norplant [9], many of our participants were informed of these issues by relatives. However, in contrast with the Norplant users who reported little direct contact with news media coverage, participants also encountered this information on their own, perhaps reflecting a secular trend of increased media exposure for adolescents.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similar to the findings of a 1997 study of adolescents using Norplant [9], many of our participants were informed of these issues by relatives. However, in contrast with the Norplant users who reported little direct contact with news media coverage, participants also encountered this information on their own, perhaps reflecting a secular trend of increased media exposure for adolescents.…”
Section: Discussionmentioning
confidence: 90%
“…Studies of DMPA [4] and Norplant [9] identified personal experiences, method characteristics, and social context (friends' experiences, sexual partnerships) as factors influencing decision-making. Additional studies of adolescents have described numerous sources for contraceptive information, primarily friends [19,20], healthcare providers [10], and family members.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15 Thus, in their contraceptive choices, women combine considerations of bodily concerns (physical functioning and experience) with personal values and beliefs. One personal value often unacknowledged by providers is some women's anxieties about hormonal contraception disrupting their "natural" bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the partner well and being able to share responsibilities were strong protective factors 18,19 . An older partner, as other surveys report 20 , should be regarded as a risk factor, because it was easier to trust him, even if he did not consider any contraceptive option.…”
Section: Relational Factorsmentioning
confidence: 97%